Combinação de nitrogênio químico e orgânico na adubação de capim-marandu - Luan Souza de Paula Gomes (2018)
Organic fertilization is a viable alternative for replacing chemical fertilizers that are more expensive and cost the production. However, release of nutrients is slow and can modify a productive response and the morphogenic patterns of marandu grass. Thus, the objective of this work was to evaluate the yield, harvests and morphogenic characteristics of irrigated marandu grass and fertilized with the combinations containing urea and bovine manure in different periods. The experiment was conducted in a randomized complete block design, with a split-plot plot of 5 treatments and 5 replications. Five levels of urea replacement by bovine manure (0; 25; 50; 75; 100% bovine manure) were tested in three growing seasons in 9-m² plots demarcated in Marandu grass. handled by cutting when capping a pre-defoliation height of 30 cm. The accumulation of forage and leaves with the inclusion of a manure in substitution of the urea reduced in 59.24% and 61.23%, respectively. The accumulated production and the number of cutting cycles decreased with the inclusion of bovine manure, in 44.7% and 46.66%. Also, the leaf elongation rate was 24% and 43% in zones 1 and 2, respectively. Leaf life increased by 23% and 52% in areas 1 and 2, respectively. The dose of the cycles was increased by 99.13% with the addition of the manure. The substitution of urea by bovine manure as nitrogen source implies an increase in yield, accumulation of forage and leaf elongation of marandu grass and increase in the duration of the harvest cycle